2021
DOI: 10.3390/rel12030162
|View full text |Cite
|
Sign up to set email alerts
|

Prison as a Site of Intense Religious Change: The Example of Conversion to Islam

Abstract: Based on the findings of mixed-methods research conducted with 279 Muslim prisoners in 10 prisons in England, Switzerland and France, this paper argues that contemporary European prisons are sites of intense religious change, in which many people born outside Islam and many born-Muslims believe in and practise Islam for the first time. In order to map this experience of intense religious change in prison, the paper articulates an original typology of conversion to identify Muslim converts as Switchers and Inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…Specifically, Latina converts expressed that Islamic practices—and wearing hijab in particular—buffered against sexualizing Latina stereotypes. Among Muslim converts in prison within the U.S. and Britain, existing research suggests that they had a high level of religious conviction, and this was related to decreased aggression, improved mental health, and better social relationships (Ammar et al, 2004; Spalek & El-Hassan, 2007; Wilkinson et al, 2021). To our knowledge, there is no study that examines these changes pre- to postconversion in MLUS converts.…”
Section: Religiousness/spirituality Factors Related To Mental Health ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, Latina converts expressed that Islamic practices—and wearing hijab in particular—buffered against sexualizing Latina stereotypes. Among Muslim converts in prison within the U.S. and Britain, existing research suggests that they had a high level of religious conviction, and this was related to decreased aggression, improved mental health, and better social relationships (Ammar et al, 2004; Spalek & El-Hassan, 2007; Wilkinson et al, 2021). To our knowledge, there is no study that examines these changes pre- to postconversion in MLUS converts.…”
Section: Religiousness/spirituality Factors Related To Mental Health ...mentioning
confidence: 99%
“…One recent study of MLUS converts found that converts actually had less conviction compared to lifelong believers and in fact struggle more with their faith (Snook et al, 2021). However, other work has demonstrated that some MLUS experience intense and notable shifts in R/S after conversion that are associated with better mental health outcomes (Wilkinson et al, 2021), and that these shifts lead to a greater identification with Islam and a deep sense of meaning (Bowen, 2009;La Voie, 2017;Maslim & Bjorck, 2009). These findings suggest that not only is more research needed to determine whether convert MLUS differ in R/S from lifelong MLUS, but that research needs to uncover more nuance in this dynamic, including how levels of R/S relate to mental health outcomes between convert and lifelong MLUS.…”
Section: The Zeal Of a Convertmentioning
confidence: 99%
“…Finally, Dix-Richardson suggested that since there was less prison violence in women's institutions, the need for protection of a group "perceived as dangerous and fearsome" (Khosrokhavar 2004, p. 38) was not as powerful a pull factor as it was for men. Other research has strongly challenged the widely held idea that Muslim males choose Islam primarily for protection, perks and privileges (Wilkinson et al 2021a).…”
Section: Researching Women and Islam In Prisonmentioning
confidence: 99%
“…The research project was subject to rigorous ethical evaluation prior to data collection (see Wilkinson et al 2021a for detailed description of methodology and ethics). The research took place in five English prisons, four Swiss prisons and one French prison in a variety of geographies, holding both sentenced and remand prisoners and covering all prison categories 1 Our research sample included all four security categories used in England and in order to ease the comparison, we adapted the equivalent security categories for use in Switzerland and France.…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation